Prospective Scenarios for Automotive Retail’s Competitivenes in Brazil in 2040 - da Rocha, Marcelo (2018)
The auto industry seems to face major changes and transformations. The sector has always been characterized by being very dynamic and pioneering in the development of new technologies, be they related to the production system or product. The pillar of this industry was built under the model of private ownership of vehicles. This scenario began to change most notably from the economic crisis of 2008 with the emergence and popularization of asset sharing platforms, which can shift vehicle ownership around the vehicle as a service. This paper focus on the future of the vehicle distribution industry in Brazil. The objective is to explore and analyze possible prospective scenarios for this industry in the country in 2040. Four scenarios were developed around the driving forces technological development and consumer behavior - Democratization of mobility, Consumer turnaround, Nothing new and Where we will stop. The study concludes that there is no doubt that the evolution of the industry is occurring and the disruption coming. While there is no certainty in any future forecast, it is quite clear that today's dealership model - based primarily on selling one vehicle at a time to individuals and then servicing those cars in their workshops - will not leave unscathed in a world of sharing, electrified, connected and autonomous vehicles.